Ernst Jünger : Leben und Werk in Bildern und Texten - Schwilk, Heimo 1952- Hrsg; Jünger, Ernst 1895-1998 Behand.Pers (Klett-Cotta, 1988)
Heimo Schwilk (Hrsg.): "Ernst Jünger". Leben und Werk in Bildern und Texten. Verlag Klett-Cotta, Stuttgart 1988. 320 S., geb., 125,- DM